A conceptual framework for integrating ecological awareness, interreligious values, and global citizenship in EFL learning - Héctor Javier Cortés Tornel (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
English Language Teaching (ELT) is increasingly expected to respond not only to linguistic needs, but also to global, cultural, and ethical challenges. In this context, ecological issues offer meaningful content for English as a Foreign Language (EFL) learning, especially when they are connected with intercultural and interreligious perspectives. This article aims to develop a conceptual framework for integrating ecological and interreligious values into EFL learning to promote ecological awareness, intercultural competence, and global citizenship. Using an integrative literature review with a conceptual-analytical approach, this study examines literature on ELT, ecological literacy, intercultural competence, global citizenship education, and interreligious ecological ethics. The analysis suggests that EFL classrooms can become spaces for developing ecological literacy through reading, writing, speaking, listening, vocabulary learning, and collaborative activities. Interreligious values such as care for creation, moderation, responsibility, solidarity, and respect for life can enrich EFL materials when presented as cultural and ethical resources rather than doctrinal instruction. This article proposes a four-dimensional conceptual model consisting of linguistic, ecological, intercultural, and ethical dimensions. The study concludes that integrating ecological and interreligious values into EFL materials can help students develop language competence while participating responsibly in a plural and ecologically fragile world by integrating linguistic, ecological, intercultural, and ethical dimensions into a unified pedagogical framework.